2021
DOI: 10.1002/nafm.10591
|View full text |Cite
|
Sign up to set email alerts
|

Explaining Channel Catfish Population Characteristics in Ohio Reservoirs

Abstract: North American fisheries management agencies commit considerable resources to managing reservoir fisheries for Channel Catfish Ictalurus punctatus, which often includes stocking. However, Channel Catfish population characteristics often vary greatly among reservoirs, resulting in variable and unpredictable fishery quality. We sampled Channel Catfish populations in 44 Ohio reservoirs with tandem, baited hoop nets to understand relationships among population characteristics (density, as CPUE from hoop nets; grow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(15 citation statements)
references
References 35 publications
0
13
0
Order By: Relevance
“…2011), which weakens the ability to quantify relationships between Channel Catfish density and other variables (Michaletz 2009; Tyszko et al. 2021). Managers can account for such variation in assessment models if this variation is predictable (Wilberg et al.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…2011), which weakens the ability to quantify relationships between Channel Catfish density and other variables (Michaletz 2009; Tyszko et al. 2021). Managers can account for such variation in assessment models if this variation is predictable (Wilberg et al.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the large differences in CPUE observed in Missouri (0–469 fish/net set; Michaletz 2009) and Ohio (5–402 fish/net set; Tyszko et al. 2021) are likely more attributable to real differences in density than to differences in catchability. However, variable catchability introduces uncertainty in the density–CPUE relationship (Flammang et al.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, they suggested that supplemental stockings may be having a deleterious effect on fisheries by slowing growth and resulting in high‐density populations comprised largely of small fish (Tyszko et al. 2021a, this special issue). The studies referenced above provide evidence that despite the large catfish management literature base, certain situations will require additional work to appropriately inform management.…”
Section: Summary Of Progressmentioning
confidence: 99%